Growth of Pongamia oinnata (L.) pierre seedlings under different levels of nitogen and phosphorus - Lo, Nyuk Thin (University Malaysia Sarawak, UNIMAS., 2013)
Pongamia pinnata or commonly known as pongam founds to be a valuable trees especially in economic and medicinal value for example as a source of biodiesel. Pongam has been planted widely in India to produce biodiesel. Due to its ability to absorb heat from the air; this tree has been used as ornamental trees at the roadside and housing area. In order to produce a success stock production, growth seedling of P. pinnata was conducted to observe and record the growth performance. There are 12 treatments involve in this study which involved treatment of nitrogen,phosphorus, and combination of both N and P where N0 is 0mg/L N, N1 is 100mg/L N, N2 is 200mg/L N, N3 is 300mg/L N, P0 is 0mg/L P, P1 is 50mg/L P, and P2 is 100mg/L P. The parameter involve are height, stem diameter, number of leaf, total leaf area, deficiency symptoms, dry root weight (DRW), dry shoot weight (DSW), and root shoot ratio. N3P1 was found to have given better result in height, number of leaf, and total leaf area which aids in the increase of yields for the oil extraction for biodiesel production.